"Betting on Women": A Feminist Political Economic Critique of Ideological Sports Narratives Surrounding the WNBA - Garcia, Christopher (The Political Economy of Communication, 2020)
Using a critical political-economic approach informed by socialist feminist methodology, this analysis enriches previous research concerning sports media representations of women's basketball. Prioritizing the narrative material provided by those who have experienced the NBAs unequal treatment of its women's league through the establishment of what was deemed the "market rate" for such a product allows one to critique the secondary status of women's sports and its normalization. Influenced by Hemmings' historiographic approach to feminist storytelling, I contend that narratives can be central to critical political-economic analysis by comparing the contested politics of the present with the supposed "truth of the past'". An example of this insight emerges from the stories of Sue Bird and Diana Taurasi detailed in ESPN's 30 for 30 podcast episode titled "The Spy Who Signed Me." By extending the focus of political economic analysis into realms of subjective, material experience, this approach seeks to empower counter-resistance narratives created by professional WNBA players while also acknowledging the structural barriers that limit their agency at meso and micro levels. While the experiences shared by Bird and Taurasi are unique to the specific historical circumstances in which they occurred, they are critical in challenging patriarchal narratives concerning the WNBA within mainstream U.S. sports media.